Sizing and analysis of pulsejet engine for unmanned aerial vehicle - Ahmadian, Sevda (2012)
The pulsejet has recently received more research interests due to its simple design,which can be developed into low-cost micro-scale propulsion devices for use in many of today as new applications such as UAVs and Unmanned Combat Vehicles (UCAV). The major obstacle for development of pulsejet engine is low efficiency of engine. The objective of this research is to investigate the possibility of using pulsejets in certain applications where the pulsejet can trade its low efficiency with low cost, simple design, and light weight. Numerical analysis is used for analysing the pulsejet engine design, This research provides many proven equations and graphs for theoretical understanding of pulsejet engine design for improving of engine performance, for this purpose the geometry of inlet, combustion chamber and tailpipe on the performance of valved pulsejet engine were studied, the effect of the environment, such as free stream speed, ambient pressure and temperature, on the performance of pulsejet engine also were explained. The main results drawn from this research is increasing efficiency and improving performance of engine by improving size of engine specially diameter of combustion chamber, To reach this result computed data(data from new design) with published data(data from previous researches) were compared.